Preparation of AlSb thin films on stainless steel flexible substrates and preventive measures of its deliquescence. (January 2021) - Li, Minqiang; Li, Bing; Zeng, Guanggen; Song, Huijin
Abstract: Flexible thin-film solar cells are important for their advantages in many aspects, and aluminum antimonide (AlSb) can be used as an absorbent layer in thin-film solar cells. However, its deliquescence limits its practical use. In this work, AlSb films were prepared by radio frequency (RF) magnetron sputtering on stainless steel flexible substrates. A flexible conformal coating membrane using acrylic resin was deposited on the AlSb films and its deliquescence prevention effect was verified. It was found that after conformal coating treatment, the deliquescence of the AlSb film was effectively stopped. The bare AlSb films and the Ni/AlSb/acrylic resin/Ni multilayer films were exposed to ambient air at the same time under the same conditions for lengths of time ranging from 1 min to 60 days. After 60 days, the bare AlSb film experienced significant deliquescence, such that the film was completely destroyed. However, the Ni/AlSb/acrylic resin/Ni multilayer films did not exhibit deliquescence.